Relative performance pay, bonuses, and job-promotion tournaments - Matthias Kräkel; Anja Schöttner (Institute for the Study of Labor (IZA), 2008)
Several empirical studies have challenged tournament theory by pointing out that (1) there is considerable pay variation within hierarchy levels, (2) promotion premiums only in part explain hierarchical wage differences and (3) external recruitment is observable on nearly any hierarchy level. We explain these empirical puzzles by combining job-promotion tournaments with higher-level bonus payments in a two-tier hierarchy. Moreover, we show that under certain conditions the firm implements first-best effort on tier 2 although workers earn strictly positive rents. The reason is that the firm can use second-tier rents for creating incentives on tier 1. If workers are heterogeneous, the firm strictly improves the selection quality of a job-promotion tournament by employing a hybrid incentive scheme that includes bonus payments.
urn:nbn:de:101:1-20081014459
Keywords: D82; 330; Bonuses; external recruitment; job promotion; limited liability; tournaments; Erwerbsverlauf; Extensives Spiel; Leistungsorientierte Vergütung; Personalbeschaffung; Hierarchie; Anreizvertrag; Theorie